The Role Of Women's Labor Force Participation In Decreasing Aceh Province Poverty Rate - Uswatun Hasanah; Annisa Ilmi Faried; Rahmad Sembiring (Yayasan Multidimensi Kreatif, 2023)
The poverty rate can decrease if there is a dual role of working women, the development of the times has proven to have implications for shifting the role of women in reducing poverty. Acehnese women, who used to be a social construction built on the basis of people's understanding of cultural values ​​and interpretations in the Islamic religion, have shifted to a new era where Acehnese women can take part in the household production process. This paper wants to analyze how big the role of women is working towards poverty reduction in Aceh Province. The results of the study show that the variable number of industries directly (X4) has a negative and not significant effect on wage estimates for Aceh Province